2010
DOI: 10.1111/j.1651-2227.2010.01688.x
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of clinical status on the association between plasma total and unbound bilirubin and death or adverse neurodevelopmental outcomes in extremely low birth weight infants

Abstract: Objectives To assess the influence of clinical status on the association between total plasma bilirubin and unbound bilirubin on death or adverse neurodevelopmental outcomes at 18–22 months corrected age in extremely low birth weight infants. Method Total plasma biirubin and unbound biirubin were measured in 1,101 extremely low birth weight infants at 5±1 day of age. Clinical criteria were used to classify infants as clinically stable or unstable. Survivors were examined at 18–22 months corrected age by cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 32 publications
1
52
1
Order By: Relevance
“…Use the lower range of the listed TSB levels for infants at greater risk for bilirubin toxicity, for example, (1) lower gestational age, (2) serum albumin levels <2.5 g dl À1 , (3) rapidly rising TSB levels, suggesting hemolytic disease and (4) those who are clinically unstable. 31 When a decision is being made about the initiation of phototherapy or exchange transfusion, infants are considered to be clinically unstable if they have one or more of the following conditions: (a) blood pH <7.15; (b) blood culture positive sepsis in the prior 24 h; (c) apnea and bradycardia requiring cardio-respiratory resuscitation (bagging and or intubation) during the previous 24 h; (d) hypotension requiring pressor treatment during the previous 24 h; and (e) mechanical ventilation at the time of blood sampling. 31 Recommendations for exchange transfusion apply to infants who are receiving intensive phototherapy to the maximal surface area but whose TSB levels continue to increase to the levels listed.…”
Section: Exchange Transfusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use the lower range of the listed TSB levels for infants at greater risk for bilirubin toxicity, for example, (1) lower gestational age, (2) serum albumin levels <2.5 g dl À1 , (3) rapidly rising TSB levels, suggesting hemolytic disease and (4) those who are clinically unstable. 31 When a decision is being made about the initiation of phototherapy or exchange transfusion, infants are considered to be clinically unstable if they have one or more of the following conditions: (a) blood pH <7.15; (b) blood culture positive sepsis in the prior 24 h; (c) apnea and bradycardia requiring cardio-respiratory resuscitation (bagging and or intubation) during the previous 24 h; (d) hypotension requiring pressor treatment during the previous 24 h; and (e) mechanical ventilation at the time of blood sampling. 31 Recommendations for exchange transfusion apply to infants who are receiving intensive phototherapy to the maximal surface area but whose TSB levels continue to increase to the levels listed.…”
Section: Exchange Transfusionmentioning
confidence: 99%
“…31 When a decision is being made about the initiation of phototherapy or exchange transfusion, infants are considered to be clinically unstable if they have one or more of the following conditions: (a) blood pH <7.15; (b) blood culture positive sepsis in the prior 24 h; (c) apnea and bradycardia requiring cardio-respiratory resuscitation (bagging and or intubation) during the previous 24 h; (d) hypotension requiring pressor treatment during the previous 24 h; and (e) mechanical ventilation at the time of blood sampling. 31 Recommendations for exchange transfusion apply to infants who are receiving intensive phototherapy to the maximal surface area but whose TSB levels continue to increase to the levels listed. For all infants, an exchange transfusion is recommended if the infant shows signs of acute bilirubin encephalopathy (hypertonia, arching, retrocollis, opisthotonos, highpitched cry) although it is recognized that these signs rarely occur in VLBW infants.…”
Section: Exchange Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, in the post-Rh isoimmunization era, it has become clear that the serum total bilirubin value correlates poorly with the subsequent development of kernicterus. There is also no single cutoff point above which an infant will categorically develop bilirubin encephalopathy and/or kernicterus, or below which a baby will remain safe [34][35][36] . Many factors, including prematurity or the presence of hemolysis, may interact with the total bilirubin to precipitate or prevent the development of kernicterus.…”
Section: Stb Versus Serum Unbound Bilirubin In the Prediction Of Kernmentioning
confidence: 99%
“…Extremely low birth weight (ELBW; <1,000 g) infants have poor outcomes; approximately 50% of these infants die or have severe neurologic deficits [1,2]. In an effort to improve these outcomes, the NICHD Neonatal Research Network assigned 1,974 ELBW infants to either aggressive or conservative phototherapy, but found that aggressive phototherapy did not improve outcomes substantially [1].…”
Section: Introductionmentioning
confidence: 99%